Social ills of (global) capitalism under scrutiny in American literature classes - Burcar, Lilijana (ELOPE (Ljubljana), 2017)
The article foregrounds the importance of honing critical literacy through socially engaged literature. Dealing with literature in an engaged and critical way can help students to develop critical thinking skills and a systemic understanding of burning social issues that inform their own living realities. Critical literary pedagogy and socially engaged literature play a key role in developing students' understanding of why and how institutional racism and institutional patriarchy constitute key operating mechanisms of capitalist social relations, which is why constructs of race and gender should never be looked upon as mere add-ons, let alone as a matter of mere culture and hence individual prejudice. In this sense, the article directly challenges the prevailing postmodernist approach in mainstream studies and teachings of literature. It calls instead for the restoration of socially engaged literature to school curricula and for a return to the contextually analytical and systemic (materialist) approach towards literature.
Keywords: capitalism; družbeno angažirana literatura; institucionalni patriarhat; institucionalni rasizem; kapitalizem; kritična pedagogika